The stimulation of the memory in escolars of the first moment of the development of the primary education - Álvarez Pérez , Mauren; López Mejías , Modesta; Orozco Pérez , Jorge Luis (Transformación, 2024)
Objective: This article aims at describing a system of continuing education activities to promote the teachers’ role in stimulating memory in primary students during the first years of development. Methods: The researchers relied on theoretical methods, such as historical-logical, analysis-synthesis, inductive-deductive; as well as empiric methods such as observation, pedagogic tests, interviewing, the analysis of documents, the learning of ten words, the reproduction of stories, the methodology of A. N. Leontiev, workshops of critical opinion and collective opinion. Results: The main contribution of the study is a system of continuing education activities that describe the role of teachers in stimulating visual-auditory memory, involuntary or voluntary memory and the semantic-logical memory of primary students during the first years of development. Conclusions: The methodological guidelines given enable educators to lead the process of memory stimulation by training high potential memory types that foster students’ learning.